Perfective -le Use and Consciousness-Raising among Beginner-Level Chinese Learners - Yi Xu (Languages, 2020)
Within the framework of explicit learning and consciousness-raising, this study investigates patterns in the use of -le in authentic classroom tasks by beginner-level learners of Chinese as a foreign language (CFL). It also explores the role and the processes of student-centered consciousness-raising in explicit knowledge building. Twenty-five participants completed a grammaticality judgment task, an interactive role-play task, and a written editing task. The experiment group received role-play sheets with explicit forms of -le provided, and participants engaged in rule induction of -le in forbidden context in the role-play session. Results showed that beginner-level learners’ difficulty with -le use manifested in different ways in these tasks, and -le underuse occurred more than overuse in the control group’s oral role-play task. Consciousness-raising through unguided small group rule induction supported participants’ learning of -le usage constraints, shown by differences between the control and experiment groups’ performances in the posttest. Through a qualitative analysis of participants’ analytical talk transcripts, the processes and outcomes of small group rule induction are examined and discussed.